Estrogen Promotes Pro-resolving Microglial Behavior and Phagocytic Cell Clearance Through the Actions of Annexin A1 - Loiola, Rodrigo Azevedo (Front Endocrinol (Lausanne), 2019)
Local production of estrogen rapidly follows brain tissue injury, but the role this hormone plays in regulating the response to neural damage or in the modulation of mediators regulating inflammation is in many ways unclear. Using the murine BV2 microglia model as well as primary microglia from wild-type and annexin A1 (AnxA1) null mice, we have identified two related mechanisms whereby estradiol can modulate microglial behavior in a receptor specific fashion. Firstly, estradiol, via estrogen receptor β (ERβ), enhanced the phagocytic clearance of apoptotic cells, acting through increased production and release of the protein AnxA1. Secondly, stimulation of either ERβ or the G protein coupled estrogen receptor GPER promoted the adoption of an anti-inflammatory/pro-resolving phenotype, an action similarly mediated through AnxA1. Together, these data suggest the hypothesis that locally produced estrogen acts through AnxA1 to exert powerful pro-resolving actions, controlling and limiting brain inflammation and ultimately protecting this highly vulnerable organ. Given the high degree of receptor selectivity in evoking these responses, we suggest that the use of selective estrogen receptor ligands may hold therapeutic promise in the treatment of neuroinflammation, avoiding unwanted generalized effects.